Ex ante analysis of impacts of iron biofortified potatoes in Peru using the Disability Adjusted Life Years (DALYs) approach - Wu, Z.; Burgos, G.; Hareau, G. (2024)
A cost-effectiveness analysis of iron biofortified potatoes in the Peruvian highlands. Estimation of disease burden employs data from the Institute of Health Metrics and Evaluation (IHME). Estimation of the effectiveness of iron biofortification on total iron absorption leverages the latest evidence - specifically from Peru - compared to non-biofortified potatoes. Estimation of adoption of iron biofortified potatoes uses several scenarios over 25 – 30 years. Two market scenarios (own consumption and diffusion to local markets) are used to estimate the size of the target population.